Redox homeostasis is compromised in vivo by the metabolites accumulating in 3-hydroxy-3-methylglutaryl-CoA lyase deficiency in rat cerebral cortex and liver. (December 2013) - da Rosa, M. S.; Seminotti, B.; Amaral, A. U.; Fernandes, C. G.; Gasparotto, J.; Moreira, J. C. F.; Gelain, D. P.; Wajner, M.; Leipnitz, G.
Abstract: 3-Hydroxy-3-methylglutaryl-CoA lyase (HL) deficiency is a disorder biochemically characterized by the predominant accumulation of 3-hydroxy-3-methylglutarate (HMG), 3-methylglutarate (MGA), 3-methylglutaconate and 3-hydroxyisovalerate in tissues and biological fluids of the affected patients. Neurological symptoms and hepatopathy are commonly found in HL deficiency, especially during metabolic crises. Since the mechanisms of tissue damage in this disorder are not well understood, in the present study we evaluated the ex vivo effects of acute administration of HMG and MGA on important parameters of oxidative stress in cerebral cortex and liver from young rats. In vivo administration of HMG and MGA provoked an increase of carbonyl and carboxy-methyl-lysine formation in cerebral cortex, but not in liver, indicating that these metabolites induce protein oxidative damage in the brain. We also verified that HMG and MGA significantly decreased glutathione concentrations in both cerebral cortex and liver, implying a reduction of antioxidant defenses. Furthermore, HMG and MGA increased 2', 7'-dichlorofluorescin oxidation, but did not alter nitrate and nitrite content in cerebral cortex and liver, indicating that HMG and MGA effects are mainly mediated by reactive oxygen species. HMG and MGA also increased the activities of superoxide dismutase and catalase in cerebral cortex and liver, whereas MGA decreased glutathione peroxidase activity in cerebral cortex. Our present data showing a disruption of redox homeostasis in cerebral cortex and liver caused by in vivo administration of HMG and MGA suggest that this pathomechanism may possibly contribute to the brain and liver abnormalities observed in HL-deficient patients.